2017
DOI: 10.1007/s11606-016-3980-z
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of Patient Engagement and Patient-Reported Outcomes in Primary Care Practices of Accountable Care Organizations

Abstract: Diabetic and CVD patients who received care from ACO-affiliated practices with more developed patient-centered cultures reported lower PHQ-4 depression symptom scores and better physical functioning. Diabetic and CVD patients who were more highly activated to participate in their care reported lower PHQ-4 scores and better physical and social outcomes of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 38 publications
3
64
0
1
Order By: Relevance
“…Physician leadership of ACOs in the US appears strong 48. Little is known about how ACOs engage patients and their families in shared decision making and improving care, but there is some evidence that patients receiving care from more patient centred practices report better outcomes 49. In England, STPs have struggled to involve clinicians, patients, and local authorities28—just like the integrated care pioneers that preceded them 50.…”
Section: Lessons For the English Nhsmentioning
confidence: 99%
“…Physician leadership of ACOs in the US appears strong 48. Little is known about how ACOs engage patients and their families in shared decision making and improving care, but there is some evidence that patients receiving care from more patient centred practices report better outcomes 49. In England, STPs have struggled to involve clinicians, patients, and local authorities28—just like the integrated care pioneers that preceded them 50.…”
Section: Lessons For the English Nhsmentioning
confidence: 99%
“…Conceptualizations of integration among ACO stakeholders may also be related to their willingness to undertake performance‐enhancing initiatives such as implementing new patient communication technologies and dedicating resources to programs for patient education and engagement (Shortell et al. ). Clarifying the ways leaders design and execute their organizational integration strategies—and the extent to which providers buy‐in to the approaches—can provide important insight into the differences in performance across organizations that are structurally similar.…”
Section: Discussionmentioning
confidence: 99%
“…Notions of what integration entails differ by ACO type, so future research examining the ways in which ACOs integrate services based on their organizational structure may aid in identifying the drivers of within-ACO type variance in quality and cost performance. Conceptualizations of integration among ACO stakeholders may also be related to their willingness to undertake performance-enhancing initiatives such as implementing new patient communication technologies and dedicating resources to programs for patient education and engagement (Shortell et al 2017). Clarifying the ways leaders design and execute their organizational integration strategies -and the extent to which providers buy-in to the approaches-can provide important insight into the differences in performance across organizations that are structurally similar.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients who reported that the organization of their primary care practice was more in line with the CCM, as measured by the Patient Assessment of Chronic Illness Care, 4 had better mental and physical health outcomes. However, this association was mediated by the degree of patient activation, as measured by the Patient Activation Measure (PAM).…”
mentioning
confidence: 99%